Noble Metal Dichalcogenides: A Noble Metal Dichalcogenide for High‐Performance Field‐Effect Transistors and Broadband Photodetectors (Adv. Funct. Mater. 5/2020). (29th January 2020) - Wang, Zhen; Wang, Peng; Wang, Fang; Ye, Jiafu; He, Ting; Wu, Feng; Peng, Meng; Wu, Peisong; Chen, Yunfeng; Zhong, Fang; Xie, Runzhang; Cui, Zhuangzhuang; et al.
Abstract : In article number 1907945, Fang Wang, Qinghua Zhang, Xiaohao Zhou, Weida Hu, and co‐workers show that 2D materials exhibit excellent properties, such as atomic thinness, tunable bandgap, and high carrier mobility. The family of 2D materials is ceaselessly diversified and enriched, especially for the recently investigated noble metal dichalcogenides. Narrow bandgap noble metal dichalcogenides with good stability have become promising candidates for fabricating high performance electronic and novel optoelectronic devices.